Pengaruh Pelayanan Muatan Petikemas terhadap Kinerja Operator RTG (Rubber Tyre Gantry) Diterminal Petikemas Koja - Octy Avriani; Dedy Dedy (Sekolah Tinggi Manajemen Transportasi (STMT Malahayati Jakarta), 2024)
In an archipelagic country, the role of ports is very important for maritime affairs. The Koja Container Terminal (TPK) has been operating since 1997 in anticipation of the increasing demand for container services in the early 1990s in line with the rapid increase in export and import activities at the Port of Tanjung Priok. Based on statistics, 90% of international trade commodity activities are carried out through sea ports and 65% through the Asia Pacific route. The field of port activities is indeed very broad, including services for ships, services for goods and many other types of services. Service activities in the container stacking yard are the key to improving ship loading and unloading services, this is because the service in the container yard is the beginning of loading and unloading activities at the port. The service process in the container stacking field hampers the performance of RTG (Rubber Tire Gantry) operators when picking up container loads.